EKSPLORASI ETNOMATEMATIKA PADA MASJID AL-AKBAR SURABAYA - Tuhfatul Janan; Pratiwi Dwi Warih Sitaresmi; Nuryami; Ratna Damayanti; Nurhidayati (LPPM STAI Muhammadiyah Probolinggo, 2023)
Ethnomathematics is the study of how mathematics is related to culture and people's daily lives. In this research, researchers used a descriptive exploratory method with an ethnographic approach. They are looking for information about mathematical concepts contained in the buildings and ornaments of the Al-Akbar Mosque of Surabaya. Several data collection techniques used include literature study, observation, and documentation. The research results show that in the buildings and ornaments of the Al-Akbar Mosque of Surabaya, there are various plane shapes (such as ellipses, squares, circles, and rectangles) and spatial shapes (such as pyramids and tubes). This research can provide a deeper understanding of how mathematical concepts are reflected in the culture and artistic architecture of religious buildings such as mosques.Keywords: Ethnomathematics, Al-Akbar Mosque of Surabaya, Geometry